2010
DOI: 10.3109/1354750x.2010.504308
|View full text |Cite
|
Sign up to set email alerts
|

CYFRA21-1 can predict the sensitivity to chemoradiotherapy of non-small-cell lung carcinoma

Abstract: CYFRA21-1 may be a reliable surrogate marker of CRT efficacy in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Cases of advanced lung cancer showed a statistically highly significant increase in CK19 than benign lung disease ( p < 0.001). This result was in concordance with results reported by Weiskopf et al [4], Ebert et al [5], Paone et al [6], Krismann et al [7], Qu et al [16], and Wang et al [17]. …”
Section: Discussionsupporting
confidence: 93%
“…Cases of advanced lung cancer showed a statistically highly significant increase in CK19 than benign lung disease ( p < 0.001). This result was in concordance with results reported by Weiskopf et al [4], Ebert et al [5], Paone et al [6], Krismann et al [7], Qu et al [16], and Wang et al [17]. …”
Section: Discussionsupporting
confidence: 93%
“…Serum CYFRA21-1 level has also been shown to predict treatment effectiveness and prognosis in patients treated with surgery, [13,14] chemotherapy, [15–17] targeted therapy, [18–20] and concurrent chemoradiation. [21] Previous studies of the association of change in serum CYFRA21-1 with response to chemotherapy, which focused on synchronous or early prediction of OR, found that it did have predictive value. [12–25] A few investigations have reported the predictive value of change in serum CYFRA21-1 with DC after the second cycle of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…About one to two million people die from lung cancer every year worldwide. Lung cancer causes more deaths than the other three most common cancers combined, i.e., colon, breast and prostate (1,2). In an attempt to describe human lung cancer, many studies have concentrated on enzyme activities (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, serum tumour markers are not useful in lung cancer diagnosis (1). The diagnosis of lung cancer is based on the histological and cytological examination of material usually obtained by bronchoscopy (endobronchial biopsies, washings, and brushings) (19).…”
Section: Introductionmentioning
confidence: 99%